2021
DOI: 10.30658/hmc.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Social Robots as the Bride? Understanding the Construction of Gender in a Japanese Social Robot Product

Abstract: This study critically investigates the construction of gender on a Japanese hologram animestyle social robot Azuma Hikari. By applying a mixed method merging the visual semiotic method and heterogeneous engineering approach in software studies, the signs in Azuma Hikari’s anthropomorphized image and the interactivity enabled by the multimedia interface have been analyzed and discussed. The analysis revealed a stereotyped representation of a Japanese “ideal bride” who should be cute, sexy, comforting, good at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The third subtype focuses on sexual interactions with software sexbots (e.g., AI-enabled chatbots; Banks and van Ouytsel, 2020 ; AI-enabled holograms; Liu, 2021 ). Those software artifacts are not tangible but invite the user to engage in social, romantic and sexual interactions and relationships.…”
Section: Sexual Interaction With Digital Technologiesmentioning
confidence: 99%
“…The third subtype focuses on sexual interactions with software sexbots (e.g., AI-enabled chatbots; Banks and van Ouytsel, 2020 ; AI-enabled holograms; Liu, 2021 ). Those software artifacts are not tangible but invite the user to engage in social, romantic and sexual interactions and relationships.…”
Section: Sexual Interaction With Digital Technologiesmentioning
confidence: 99%
“…The discussions on the subreddit showed that the ideal bot girlfriend corroborated classical and contemporary gender imaginaries, some of which have been identified in textual analyses of AI and robot discourses (Leyda, 2016; Liu, 2021; Phan, 2019; Strengers and Kennedy, 2021), such as women being pretty, cute, and sexy as well as manipulative and hurtful. Many conversations also repeated postfeminist discourses (Gill, 2007), from a male perspective, of sexual assertiveness and ostensibly independent preference for male interests, such as manga, anime, and basketball.…”
Section: Findings: Ai and Gender Imaginaries In Parallel Linesmentioning
confidence: 68%
“…The femininity tropes assigned to the bots involve intentional stupidity (Liu, 2000), helplessness (Pietronudo, 2018), servitude (Phan, 2019;Zdenek, 2007), and childlikeness (Wood, 2002) and some of them were corroborated in our findings as well. One of the crucial features of fembots is the interplay between hyperfeminized innocent cuteness and sexiness (Leyda, 2016;Liu, 2021) and these tropes were also evoked by the Redditors we studied. However, while the gendering of bots is often clichéd, research suggests that fembots cannot be reduced to a single gender norm as they present a wide array of culturally embedded gender imaginaries (Pietronudo, 2018;Zdenek, 2007).…”
Section: Ai and Gender Imaginariesmentioning
confidence: 86%
“…The NAO robot serves as a versatile platform for diverse interactive tasks, using speech, gestures, and other interactive behaviors to engage users. Its role within the project involves acting as a coach, providing guidance and support to elderly users; Gatebox, a device that generates a visual representation (hologram) of a virtual coach through a 3D effect [ 38 ]. The Gatebox hologram projects an avatar’s image, enabling an interactive coaching experience.…”
Section: Platform Componentsmentioning
confidence: 99%
“…Gatebox, a device that generates a visual representation (hologram) of a virtual coach through a 3D effect [ 38 ]. The Gatebox hologram projects an avatar’s image, enabling an interactive coaching experience.…”
Section: Platform Componentsmentioning
confidence: 99%